Propuesta de mejora en la gestión administrativa de la dirección de control de vivienda, MIDUVI en el cantón Portoviejo–Manabí - Hidrovo Zambrano, Job Jesús (2021)
The present work of Improvement Proposal to the administrative management of the MIDUVI Housing Control Directorate in the Portoviejo canton; sought to diagnose the reality of MIDUVI is management in the fase of the consequences of the 2016 earthquake and establish the perception of the public about that management, if the MIDUVI really lived up to the critical situation in Portoviejo, and complied with what is established by the Constitution and the All a Life plan, which precisely promote a decent home and life for Ecuadorians. There search was applied fundamentally to the victims of Portoviejo, for which both qualitative and quantitative methodological tools were used, in order to obtain a clearer perception, specifically, surveys of the victims were used to collect information and interviews with specialists in social management to address and analyze the results of the MIDUVI management. The objectives set out in there search were to diagnose the management of the MIDUVI, establish the perception ofthe public and elaborate the improvement proposal. The investigation began with the análisis of the management of MIDUVI, which worked to generate a social and economic reactivation that allows the victims to recover and continue their daily lives. However, it was concluded that the administrative management did not generate results and there were various disagreements on the part of the victims, especially an unmet demand, insuch a way that to attend to the victims in anagile and fairway, with out neglecting any sector, It must guarantee optimal, honest and efficient administrative management, through the improvement plan to the control department of the institution in charge.